Utilization of honey bee broods with potential sustainable food in Yucatan, Mexico - García López, Daniel; Moguel Ordóñez, Yolanda; Chel-Guerrero, Luis Antonio; Betancur-Ancona, David Abram (Revista Colombiana de Investigaciones Agroindustriales, 2024)
By 2050, the world will be home to more than 9 billion people, thus doubling the food demand. Currently, food production is based on practices such as livestock farming, agriculture, and fishing that require large amounts of non-renewable resources, making it unsustainable. Given this, there is a need to investigate other emerging food sources or ingredients that could provide nutritional components for the growing population. The objective of this work was to review various topics related to entomophagy, particularly to Apis mellifera brood produced in Yucatan Mexico, and analyze their relationship with food security, sustainability, marketing, and the nutritional contribution of insects with food potential. The information from books, review articles and research studies obtained from academic repositories related to A. mellifera bee brood was analyzed, published from 2002 to date and of which full access was obtained in search engines such as: Google Scholar, Scielo, ResearchGate, PubMed, Redalyc, Web of Science and ScienceDirect. The results showed that, due to their wide presence and nutrient content, the consumption of bee broods (larvae and pupae), particularly drones, is recommended since these are a potential source of protein, fat, and minerals. Beekeeping is part of the livestock activities, with more than 2 million hives in production in Mexico and about 250,000 in the Yucatan Peninsula alone. Honey bee broods could represent a product of interest that could provide added value within the hive products along with honey, wax, royal jelly, propolis, and apitoxin since it is a potential unexploited food that could be estimated at thousands of metric tons (MT) annually. Information on the chemical and nutritional composition of the brood at different stages of development of the honey bee is essential to endorse the species as food.